2010
DOI: 10.1016/j.math.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic girdle pain, clinical tests and disability in late pregnancy

Abstract: The objective of this cross-sectional study was to explore the associations between pain locations, responses to the posterior pelvic pain provocation (P4) test, responses to the active straight leg raise (ASLR) test and disability in late pregnancy. 283 women in gestation week 30 (mean age 31.3 years; 59% nullipara) completed a questionnaire (including pain drawing and Disability Rating Index, DRI). A physiotherapist blinded for the questionnaire data assessed responses to the P4 and ASLR tests. The pain draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
97
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 40 publications
3
97
0
Order By: Relevance
“…This subgroup has been associated with greater functional disability, more frequent sick leave, and significantly worse prognosis than pain in one or two pelvic locations. 2,3,28 Furthermore, it has previously been shown that the number of pain sites has a strong predictor utility. 9 This strengthens our classification of severity level during pregnancy, which was based on pain intensity, pain location, and the number of pain sites.…”
Section: Discussionmentioning
confidence: 99%
“…This subgroup has been associated with greater functional disability, more frequent sick leave, and significantly worse prognosis than pain in one or two pelvic locations. 2,3,28 Furthermore, it has previously been shown that the number of pain sites has a strong predictor utility. 9 This strengthens our classification of severity level during pregnancy, which was based on pain intensity, pain location, and the number of pain sites.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies 15,16 suggest that predictors of poor recovery from symptoms post partum include older age, work dissatisfaction and the presence of combined low back pain and PGP in comparison with pain in either location alone. There is some evidence that women with combined pubic symphysis pain and bilateral posterior PGP in pregnancy have a slower recovery than those women with fewer pain locations 12,16 and that women with a high number of other bodily pain sites are more likely to have high pain intensity scores and postpartum non-recovery. 17 Guidelines 3 suggest risk factors for PGP include a previous history of low back pain and previous trauma to the pelvis.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…It is a musculoskeletal pain located within the pelvic area between the posterior iliac crest and gluteal folds, with or without leg pain [8] . Prevalence estimates for PGP range widely from 20% overall [8] 35-50% in early pregnancy and 60%-70% in late pregnancy [9,10] . For 25 to 30% of pregnant women the problem becomes severe [1,2,11] .…”
Section: Introductionmentioning
confidence: 99%